Fireworks: How to Simulate the Manufacture and Operation in the Atmosphere with the Substitution of Ultrasonic Spray Pyrolysis - Rudolf, Rebeka; Ferčec, Urban; Shariq, Mohammed (Current Nanoscience, 2019)
Background: This review provides a closer look at recent work in the field of fireworks manufacture, which could see the replacement of micron-sized particles with their nano-scaled counterparts. Moreover, we also discuss micron-sized particles as well as nanoparticles (NPs) from K, Fe, Al, Ti, Ba, etc., that are produced in the atmosphere as a result of these fireworks. One of the possible technological substitutes for fireworks is presented in detail, i.e., the use of ultrasonic spray pyrolysis (USP) technology. Method: We searched Google, Web of Science and PubMed for a literature survey of fireworks and their products: firecrackers, micron-sized and nanoparticles. Moreover, we used some of our own knowledge and experimental data to strengthen the possibility of simulating the synthesis of firework products on the laboratory scale. Results: The use of nano reactants and oxidisers has seen a substantial increase in the sound efficiency and a decrease in the amount of chemicals used, making fireworks more eco-friendly. The application of Al- and Ti-based nano flash powder in the size range from 35 nm to 50 μm resulted in a significant improvement in the ignition properties of the fireworks. Under changing aerodynamic conditions, it is difficult to collect them as samples for real-time monitoring, needed for their characterization or the testing of their harmfulness under laboratory conditions. As a result, NPs below 100 nm in the surroundings could be easily inhaled into the lungs and cause more pulmonary and respiratory problems than micron-sized particles. USP produces nanoparticles in the laboratory that could replace the conventional micron-sized firecracker raw materials, or nanoparticles that are similar to those formed by fireworks. It will also help to identify the physiochemical properties of the airborne particulates in order to understand and evaluate their impact. This review could be valuable for a controlled economic synthesis through USP, and in the use of nanopowders in pyrotechnology that could reduce pollution to a great extent, thus contributing to the growth and good practise of the fireworks industry. With respect to the USP synthesis, we have also discussed in detail the physical (size, shape) and chemical (composition) characteristics of Al2O3 and TiO2 NPs from different precursors and their temperature ranges. An in-depth explanation for a comparative analysis for the formation mechanism of nanoparticles through both fireworks and USP is presented in the final section. Conclusion: We can produce nanoparticles in the laboratory with ultrasonic spray pyrolysis that have similar properties to those produced from fireworks and can then be used for further testing.
Keywords: nanoparticles